2012
DOI: 10.5194/hess-16-147-2012
|View full text |Cite
|
Sign up to set email alerts
|

Frequency pattern of turbulent flow and sediment entrainment over ripples using image processing

Abstract: Abstract. River channel change and bed scourings are source of major environmental problem for fish and aquatic habitat. The bed form such as ripples and dunes is the result of an interaction between turbulent flow structure and sediment particles at the bed. The structure of turbulent flow over ripples is important to understand initiation of sediment entrainment and its transport. The focus of this study is the measurement and analysis of the dominant bursting events and the flow structure over ripples in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In contrast, during the erosion phase (Tide 4), turbulence was likely stronger during very shallow flows, because the erosion rate was higher (Figure ). However, numerous studies have found that ripples develop as a result of local turbulent events acting across the interface between the erodible bed and water (e.g., Bartholdy et al, ; Bose & Dey, ; Coleman & Melville, ; Raudkivi, ; Williams & Kemp, ), with ripple formation and destruction being linked to local bursting events such as sweeps and ejections (e.g., Best, ; Gyr & Schmid, ; Keshavarzi et al, ; Schindler & Robert, ). Thus, we can infer that the high accretion rate and relatively weak turbulence of VSWS during the accretion phase would lead to a decrease in ripple height (Table ; ripple destruction), whereas the high erosion rate and relatively strong turbulence of VSWS during the erosion phase would lead to an increase in ripple height (Table ; ripple formation).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, during the erosion phase (Tide 4), turbulence was likely stronger during very shallow flows, because the erosion rate was higher (Figure ). However, numerous studies have found that ripples develop as a result of local turbulent events acting across the interface between the erodible bed and water (e.g., Bartholdy et al, ; Bose & Dey, ; Coleman & Melville, ; Raudkivi, ; Williams & Kemp, ), with ripple formation and destruction being linked to local bursting events such as sweeps and ejections (e.g., Best, ; Gyr & Schmid, ; Keshavarzi et al, ; Schindler & Robert, ). Thus, we can infer that the high accretion rate and relatively weak turbulence of VSWS during the accretion phase would lead to a decrease in ripple height (Table ; ripple destruction), whereas the high erosion rate and relatively strong turbulence of VSWS during the erosion phase would lead to an increase in ripple height (Table ; ripple formation).…”
Section: Discussionmentioning
confidence: 99%
“…Quadrant analysis was used to investigate the nature of flow motions in the near‐ bed region and is based on the joint distribution of the velocity fluctuations u ' and v ' from the mean streamwise and vertical components (Lu and Willmarth, ) : u' = u – trueu¯ and v' = v –truev¯, where u and v are instantaneous velocities and trueu¯ and truev¯ are mean velocities. Quadrants 2 and 4 have been associated with ejection‐ and sweep‐like flow motions, respectively, and thence with sediment entrainment in rivers (Drake et al ., ; Nelson et al ., ; Dey et al ., ; Keshavarzi et al ., ). In this analysis, a magnitude threshold or “hole” size of zero was selected when computing the proportion of time spent in each quadrant.…”
Section: Methodsmentioning
confidence: 99%
“…In past, many researchers used mean velocity to describe transport phenomena; however, actual turbulent flow can be described by estimation of fluctuating components of velocity in appropriate directions. Many studies were reported previously for finding the instantaneous velocity components using hot-film anemometer (Nakagawa and Nezu 1977), ADV (Carollo et al 2005;Ball 1997, 2007;Keshavarzi and Shirvani 2003;Keshavarzi et al 2005Keshavarzi et al , 2012Mazumder 2012, 2013;Mazumder et al 2011;Ramesh and Kothyari 2013;Ramesh et al 2011;Song and Chiew 2001). The Laser Doppler Velocimeter, LDV, was also used by investigators (Balachandar and Bhuiyan 2007;Balachandar and Patel 2002;Chen and Chiew 2003;Kirkgoz 1989;Nelson et al 1995;Nezu and Rodi 1986;Papanicolaou et al 2001), in the past, in quantifying the turbulent flow characteristics over channel bed.…”
Section: Introductionmentioning
confidence: 96%